RF photogun and Cherenkov decelerating system for a high power radiation source in sub-mm region - Bashmakov, Yu.A.; Bondarenko, T.V.; Komarov, D.A.; Polozov, S.M.; Rashchikov, V.I.; Shchedrin, I.S.; Smirnov, A.V.; Voronkov, A.V.; Tishchenko, A.A. (Вопросы атомной науки и техники, 2012)
Some results of RF photogun and Cherenkov decelerating system research and design are discussed. This R&D is providing to construct a high power pulse radiation source in sub-mm region. It is well known that the conducting capillary filled by dielectric skin can be used as a Cherenkov radiation generator. One needs very short (less than 1 mm) and high brightness electron bunch to provide the coherent radiation. The short bunch can be generated by means of a photogun. The electrons should be accelerated to the energy equal to 1…4 MeV in compact section and injected to the decelerating structure. This radiation source can be used for inspection systems or as a laboratory generator. Рассмотрены некоторые результаты исследования и разработки СВЧ-фотокатода и черенковской замедляющей системы, предназначенных для генерации мощных импульсов излучения субмиллиметрового диапазона. Как известно, проводящий капилляр, покрытый изнутри слоем диэлектрика, может быть использован в качестве источника черенковского излучения. Для получения монохроматического излучения необходимо иметь очень короткий (меньше 1 мм) сгусток электронов, который может быть получен при использовании фотокатода. Электроны должны быть ускорены в короткой системе до энергии 1…4 МэВ и инжектированы в замедляющую систему. Такой источник излучения может быть использован в досмотровой системе или в качестве лабораторного генератора. Розглянуто деякі результати дослідження та розробки НВЧ-фотокатода і черенківської уповільнюючої системи, призначених для генерації потужних імпульсів випромінювання субміліметрового діапазону. Як відомо, проводячий капіляр, покритий зсередини шаром діелектрика, може бути використаний як джерело черенківського випромінювання. Для отримання монохроматичного випромінювання необхідно мати дуже короткий (менше 1 мм) згусток електронів, який може бути отриманий при використанні фотокатода. Електрони мають бути прискорені в короткій системі до енергії 1…4 МеВ і інжектовані в уповільнюючу систему. Таке джерело випромінювання може бути використано в оглядовій системі або в якості лабораторного генератора.